Maternity and childcare leave and the struggle for equal reghts in Korean labor market - Baek, Song Yi (KDI School, 2011)
Despite availability of a maternity and childcare leave system, female workers in the Korean labor market are forced to choose between motherhood and their career as they face great difficulty in utilizing the system. This paper examines such difficulty by exploring the historical marginalization of female workers from which the difficulty emerged and by analyzing various cases of difficulties experienced by workers from government, scholarly articles and media reports. The findings suggest the male-centric workplace culture is one of the major factors that obstruct the usage of the leave system. To challenge the current workplace culture, I suggest that an effective government monitoring of workplaces with regard to the maternal protection laws and a combined effort of government, women’s organizations, and labor unions are necessary along with the collective demands of female workers.
Thesis(Master) --KDI School:Master of Public Policy,2011